Z dziejów gospodarczych Bydgoszczy w okresie międzywojennym. Zakłady i Warsztaty Precyzyjno-Mechaniczne i Optyczne Krzymień i Paszke 1927-1939 (Kronika Bydgoska, 2017)
The article describes the foundation and activity of the Krzymień and Paszke Precision-Mechanics and Optical Plants and Workshops in Bydgoszcz. The small workshop established in October 1927 turned to a company, which in the years before the outbreak of the war employed about 50 workers. After 1945, it transitioned to one of the biggest industrial plants of Bydgoszcz - TELKOM-TELFA Tele Electronics Works. The report explains the circumstances of establishing the company and the initial period of its operation, production volumes, sales, employment and wages during the interwar period, and a brief outline of the history of the company during World War II. It presents individual stages of development of the company, from getting first orders and early expansion of production facilities, through a period of stagnation and struggle for survival during the Great Depression in the beginning of the 1930s, followed by the prosperity period and related expansion of the plant and intensification of production. The Krzymień and Paszke serves as a typical example of business activity and history of small enterprises in prewar Bydgoszcz.